Arthrospira Cell Residues for Lactic Acid Fermentation as Bioproducts From Waste Utilization - Pan-utai, Wanida; Thitiprasert, Sitanan; Pornpukdeewattana, Soisuda (Frontiers in Energy Research, 2022)
Arthrospira (Spirulina) platensis is a freshwater cyanobacterium that is commercially produced as a food source on a global scale and considered safe for human consumption. After C-phycocyanin (C-PC) extraction, the waste cell residue (WCR) is composed of nutrients with 30% protein content. Here, the potential of WCR as a nitrogen source for Bacillus coagulans cultivation and bioproducts was evaluated. Nitrogen substitute from WCR under different conditions of 20—100 g L−1 was performed. B. coagulans cultivation was achieved with maximal viable cells at 7.6–9.5 log CFU mL−1. Increasing WCR gave decreasing lactate production. The highest lactate production at 27 g L−1 was achieved from WCR 20 g L−1, highlighting the potential use of A. platensis waste biomass residue as a nitrogen source for the growth of lactic acid bacteria and zero-waste biotechnology methodology. The utilization of renewable resources is a crucial step toward developing a sustainable industrial society.